Single-cell Analysis of Bacillus subtilis Biofilms Using Fluorescence Microscopy and Flow Cytometry - Garcia-Betancur, Juan C. (MyJove Corporation, 2012)
Biofilm formation is a general attribute to almost all bacteria( 1-6). When bacteria form biofilms, cells are encased in extracellular matrix that is mostly constituted by proteins and exopolysaccharides, among other factors (7-10). The microbial community encased within the biofilm often shows the differentiation of distinct subpopulation of specialized cells (11-17). These subpopulations coexist and often show spatial and temporal organization within the biofilm ( 18-21). Biofilm formation in the model organism Bacillus subtilis requires the differentiation of distinct subpopulations of specialized cells. Among them, the subpopulation of matrix producers, responsible to produce and secrete the extracellular matrix of the biofilm is essential for biofilm formation (11,19). Hence, differentiation of matrix producers is a hallmark of biofilm formation in B. subtilis. We have used fluorescent reporters to visualize and quantify the subpopulation of matrix producers in biofilms of B. subtilis(15,19,22-24). Concretely, we have observed that the subpopulation of matrix producers differentiates in response to the presence of self-produced extracellular signal surfactin (25). Interestingly, surfactin is produced by a subpopulation of specialized cells different from the subpopulation of matrix producers (15). We have detailed in this report the technical approach necessary to visualize and quantify the subpopulation of matrix producers and surfactin producers within the biofilms of B.subtilis. To do this, fluorescent reporters of genes required for matrix production and surfactin production are inserted into the chromosome of B. subtilis. Reporters are expressed only in a subpopulation of specialized cells. Then, the subpopulations can be monitored using fluorescence microscopy and flow cytometry (See Fig 1). The fact that different subpopulations of specialized cells coexist within multicellular communities of bacteria gives us a different perspective about the regulation of gene expression in prokaryotes. This protocol addresses this phenomenon experimentally and it can be easily adapted to any other working model, to elucidate the molecular mechanisms underlying phenotypic heterogeneity within a microbial community.